(3GdeSGFds - (3eMeO Hf CMeO Hf CMeO Hf QTO GdeGdcj GdbQWHj GdCfOdSj, GdbGVj CHh GdhdjO (B( (3GdLO (B)(3, J (B520 (3g` s
(3ChdgG (B:s
(3CeG eG PcQJe ef ETJQW GdMcje ai GdHQGgjf Cf Jchf eMehdGJgG Chdjg aEfg jfHZi Cf jage ef ETJQGWg ai GdeMehdGJ Cf Jchf NGUI ai eMehdGJ GdebOeGJ CfaSgG heMehdGJ GdeWGdH s
(3BNQgG (B:s
(3CcedJ gPG Gdbhd jhe GdCMO GdYGTQ ef ThGd SfI SHY hSJjf hNeSeGFI , hPdc HeOjfI ETHjdjI , LHQgG Gddg JYGdi HaVdI cedJ GdeSGFd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3hgj ef cJH GdCejQ RjOGf GdMSfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B228s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(632/4) s
Keywords: (3GdadSaI hGdefWbs